Kajian Beberapa Sistem Tanam Berbeda Terhadap Pertumbuhan Dan Produksi Padi Sawah Varietas IR-64 - Kadek Indah Sri Lestari; Anggia Anggia (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
Farmers in cultivating rice (oryza sativa L.) currently still apply conventional systems so that productivity is not optimal. It is known that there are still some plant cultivation systems that have not been used to maximize the cultivation of IR64 rice varieties. This study aims to determine the effect of different cropping systems on the growth and production of lowland rice IR64 varieties. This research was conducted from February to April 2020 at the Ngkari-ngkari Village, Bungi District, Baubau City. This study used a randomized block design (RAK) consisting of three replications with seven treatments for the Tile Planting System (T0), Legowo Planting System (T1), Indri Planting System (T2), Spread Planting System (T3), Hazton Planting System (T4). ), Triangular Planting System (T5) and Tegel Tapin Planting System (T6). The data analysis used was the analysis of variance (ANOVA) with the BNJ further test at the 95% confidence level. The parameters of this research include plant height, leaf area, number of productive tillers, weight of 1000 seeds, relative growth rate (LTR) and productivity of GKG. The results showed that the leaf area parameters and productivity of rice paddy GKG were IR64 rice varieties has a significant effect while on the parameters of plant height, number of productive tillers, weight of 1000 grains of grain, relative growth rate (LTR) has no significant effect. ton haˉ¹).